Campomelic dysplasia associated with a de novo 2q;17q reciprocal translocation. - Young, I D (1992)
A phenotypically female fetus with campomelic dysplasia and a de novo reciprocal translocation, 46,XY,t(2;17) (q35;q23-24), is presented. This is the second case of campomelic dysplasia in which a rearrangement involving the long arm of chromosome 17 has been identified, indicating that this is likely to be the site of the campomelic dysplasia locus.